Implementasi Blockchain Quorum Berbasis IBFT dalam Pengamanan dan Integritas Log Aktivitas Server - Nugroho Adi Prasetyo; Sarwido Sarwido; Gentur Wahyu Nyipto Wibowo (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This research uses a blockchain-based system for audit logging that relies on Quorum IBFT to ensure that data can't be altered and to handle potential server failures. The AuditLog smart contract was placed on a network of 7 validators, all of which were connected to each other. Logs were processed in batches every 5 minutes, which led to a logging rate of 0.0954 logs per second, or about 8,244 logs each day, with an efficiency gain of 2 to 9 times. When analyzing 651 transactions, the average time to confirm a log was 6.16 seconds, and 81.8% of them were confirmed within 2 to 5 seconds. Tests showed that the system can handle up to 2 failed nodes, but if 3 nodes stop working, the system can't reach agreement and stops creating new blocks, proving that the IBFT system works as intended. The system also sends real-time alerts via Telegram every 5 seconds, giving early warnings about any problems. A review of the smart contract confirmed that it can't be changed because it doesn’t have functions like editLog(), deleteLog(), or updateLog(). The contract has five functions: addLog, addLogBatch, getLog, getLogCount, and logs. These only allow adding data or viewing it, ensuring that logs are permanent and can’t be changed, with proof through cryptographic transaction hashes. This solution provides better audit trails than traditional databases because it uses built-in immutability, transparency across a network, cryptographic proof that can't be denied, and the ability to handle server failures. It is suitable for important systems like government infrastructure, financial systems, and security monitoring.